2021
DOI: 10.1136/bmjopen-2020-043227
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and associated factors of suicidal ideation and attempt among people with epilepsy attending outpatient treatment at primary public hospitals in northwest Ethiopia: a multicentre cross-sectional study

Abstract: ObjectiveThis study aimed to assess magnitude and associated factors of suicidal ideation and attempt among people with epilepsy attending outpatient treatment at primary public hospitals, northwest Ethiopia using suicide module of World Mental Health Survey initiative version of the WHO, composite international diagnostic interview.DesignMulticentre-based cross-sectional study was used.SettingData were collected using face to face interview from patients with epilepsy who attended outpatient treatment at prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…This study is similar with previous studies in USA (20) ,Colombia, (21), Brazil (22), China ( 10) Nepal (11), Washington (23), Canada, (24), Bosnia and Herzegovina, (25), Poland, (26), Brazil (27), Malaysia(28) ,, South Africa (29), Nigeria (30), Eriteria (8 ), in India (31), Ethiopia (32)(33)(34)(35), Addis Ababa Ethiopia (36) This may be due to high depressive symptoms that are related to suicidal risk and thoughts.…”
Section: Discussionsupporting
confidence: 91%
“…This study is similar with previous studies in USA (20) ,Colombia, (21), Brazil (22), China ( 10) Nepal (11), Washington (23), Canada, (24), Bosnia and Herzegovina, (25), Poland, (26), Brazil (27), Malaysia(28) ,, South Africa (29), Nigeria (30), Eriteria (8 ), in India (31), Ethiopia (32)(33)(34)(35), Addis Ababa Ethiopia (36) This may be due to high depressive symptoms that are related to suicidal risk and thoughts.…”
Section: Discussionsupporting
confidence: 91%
“…This study is similar with previous studies in USA (20) ,Colombia, (21), Brazil (22), China (10) Nepal (11), Washington (23), Canada, (24), Bosnia and Herzegovina (25), Poland (26), Brazil (27), Malaysia (28), South Africa (29), Nigeria (30), Eriteria [8], in India (31), Ethiopia (32)(33)(34)(35), Addis Ababa Ethiopia [36]. This may be due to high depressive symptoms that are related to suicidal risk and thoughts.…”
Section: Discussionsupporting
confidence: 91%
“…Suicide risk factors in epileptic patients include age, gender, socioeconomic factors, a history of psychiatric disorders and factors related to epilepsy itself (Giambarberi and Munger Clary, 2022). Suicide risk tends to decrease with age and is highest among adolescents with epilepsy (Christensen et al, 2007;Nigussie et al, 2021). In the population analysed in the present study, suicidal ideations were more common in women, even independently of depression (Kim et al, 2020;Nigussie et al, 2021), while more suicide attempts and suicides were observed among men (Abraham et al, 2019).…”
Section: Suicide Risk Factors In Patients With Epilepsymentioning
confidence: 59%